Mg/Al double layer hydroxides: intercalation with H3[α-PW12O40]•nH2O - Yuliza Hanifa; Neza Rahayu Palapa (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2016)
It has been done the intercalation of polyoxometalate H3[α-PW12O40]•nH2O on Mg-Al double layer hydroxide by comparison weight ratio of double layer hydroxides : polyoxometalate H3[α-PW12O40]•nH2O, i.e: 1:1, 1:2, 1:3 and 1: 4. The product of intercalated double layer hydroxide was characterized using FT-IR spectrophotometer, XRD, and TG-DTA analysis. The spectrophotometer results of FT-IR shown the process of intercalation was not optimum for every weight ratio. Characterization using XRD showed the process of intercalation was optimum at a ratio 2:1 that indicated at the area of 11,12o, 22,85o and 34,5o as double layer hydroxide and at the area of 60-63o showed the double layer hydroxide has intercalated with polyoxometalate. The characterization results using TG-DTA analysis at the comparison 2:1 showed loss of OH in the layer at 170 to 220°C and for the decomposition of polyoxometalate H3[α-PW12O40]•nH2O at 300 to 400°C. Keywords: Double Layer Hydroxide, Intercalation, Polyoxometalate H3[α-PW12O40]·nH2O